MR Evaluation of Vestibulocochlear Anomalies Associated with Large Endolymphatic Duct and Sac - Davidson, H. Christian; Harnsberger, H. Ric; Lemmerling, Marc M.; Mancuso, Anthony A.; White, David K.; Tong, Karen A.; Dahlen, Richard T.; Shelton, Clough (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Large endolymphatic duct and sac (LEDS) is one of the most common anomalies seen in patients with congenital sensorineural hearing loss (SNHL), and is known to occur with other inner ear findings. Our purpose was to use high-resolution T2-weighted fast spin-echo (FSE) MR imaging to describe the features and prevalence of specific anomalies that occur in association with LEDS.METHODS: We retrospectively reviewed MR images of the inner ear obtained in 63 patients with LEDS and in 60 control subjects. We evaluated each image for features of cochlear and vestibular dysplasia, including deficiency of the cochlear modiolus, gross cochlear dysmorphism, asymmetry of the cochlear scalar chambers, enlargement of the membranous vestibule, gross vestibular dysmorphism, and abnormality of the semicircular canals (SCC).RESULTS: Cochlear anomalies were present in 76% of ears with LEDS. Modiolar deficiency, gross dysmorphism, and scalar asymmetry were seen in 94%, 71%, and 65% of abnormal cochleas, respectively. Vestibular abnormalities were present in 40% of ears with LEDS. Simple enlargement, gross dysmorphism, and distortion of the lateral SCC were seen in 84%, 16%, and 32% of abnormal vestibules, respectively.CONCLUSION: Coexistent cochlear anomalies, vestibular anomalies, or both are present in most ears with LEDS, and appear as a spectrum of lesions, ranging from subtle dymorphism to overt dysplasia. The presence of coexistent anomalies in LEDS affects treatment decisions and prognosis. Newer techniques of high-resolution FSE MR imaging provide a means of exquisite characterization of LEDS, as well as more sensitive detection of associated vestibulocochlear anomalies.